Drug used pattern by self-medication among the RT-PCR positive health workers in Dhaka city - Sharmin, Elora; Begum, Sharmin; Afreen, Swarmita; Islam, Diana; Ahmed, Sheikh Foyez (International Journal of Basic & Clinical Pharmacology, 2021)
Background: To date there is no effective treatment against COVID-19. Self-medication played one of the major modes of treatment among general population as well as the health workers during this pandemic. Studying the pattern of self-medication among the health care workers (HCWs) may indicate their knowledge and skills towards rational use of medicines. The aim of the study was to assess the pattern self-medication among the COVID-19 affected HCWs. Methods: This cross-sectional survey assessed the pattern of drug used by self-medication among the health workers who were RT-PCR positive in context to Bangladesh. Results: A total of 267 HCWs data were collected. Most of the HCWs were in middle age group between 31-40 years with the mean age of 32.2±5.2. Doctors (83.9%) enrolled five times more than the nurses (16.1%). Most of the HCWs (60.3%) commenced medications just after appearance of symptoms and 27.0% went for the RT-PCR testing. Only 3.7% went to health care facilities for treatment. More than sixty percent of the respondents took medication by themselves just after start the symptoms, 19 (33.7%) took advised from the specialists and attended at health facilities 2.6%. Most of the patients (42.7%) used azithromycin as antimicrobial agent. Paracetamol was the most used drug among the participants (78.65%) followed by antihistamines (67.79%). Average number of drugs used by patients 3.1% and percentage of antibiotics per patients 42.6%. Conclusions: The prescribing practice of antibiotics shows deviation from the standard recommendation. Awareness regarding essentials drug list should be needed.